Vibration suppression method of humanoid flexible arm based on model-free predictive control. (3rd April 2021) - Du, Qinjun; Song, Chuanming; Ding, Wei; Zhao, Long; Luo, Yonggang
ABSTRACT: The commutation torque ripple of the joint drive motor in the humanoid flexible arm provides significance to the stability of the arm joints. Here, we established a model of the joint drive system to explain the influence of driving motor output torque on joint motion state and analyzed the mechanism of commutation torque pulsation. This general model of the drive system was established based on a model-free predictive control method. By deducing the universal model equation of the arm joint drive motor control system and using it as the prediction model, the optimal switching state is selected by the value function to maintain the constant phase current value of the non-commutation winding of the drive motor. Then, by using MATLAB/Simulink, a simulation model was built to verify the effectiveness of the proposed method. GRAPHICAL ABSTRACT: